Isolation and characterization of toxins from conus textile venom - Ramilo, Cecilia A.
Sequential extraction of Conus textile venom with acetic acid, distilled water and ammonium acetate gave toxins which were all lethal to mice when injected intracerebrally. Comparatible values of LD50 for acetic acid crude venom extract (CVE) (39.9 mg protein/kg mouse) and NH4Ac CVE (42.7 mg/kg_ were obtained while distilled water CVE appeared to be more lethal (24 mg/kg). Seven, six and four toxic fractions were resolved on gel filtration of acetic acid CVE, distilled water CVE and ammonium acetate CVE, respectively. Most of these toxins were found to have apparent molecular weights of less than 1400. All the fractions bioassayed were lethal to mice. Activities of the Sephadex G-25 fractions were not quite distinct. Two or more fractions of the three different crude venom extracts showed similar activities. Further separation of Sephadex G-25 fractions revealed the presence of at least 14 components. The activities of individual HPLC fractions were not distinct but some fractions showed unique activities. The HPLC fractions were less toxic and produced lethal effects at a later time than the composite Sephadex G-25 fraction. Two partially purified toxins (AA-III and NA-II) were characterized. But toxins were inactivated by dithiothreitol, suggesting the presence of disulfide bridges. NA-II (ammonium acetate fraction) was inactivated by trypsin and chymotrypsin while AA-III (acetic acid fraction) was not inactivated by the proteases. NA-II was inactivated by heat while AA-III was not. Both AA-III and NA-II was inactivated by heat while AA-III was not. Both AA-III and NA-II fractions effected a sleep-like state in mice. However, these toxins seem to have structures which bear little or no similarity to the ?sleeper? peptide from Conus geographus.